IL-33 promotes recovery from acute colitis by inducing miR-320 to stimulate epithelial restitution and repair - Lopetuso, Loris R. (Proc Natl Acad Sci U S A, 2018)
Defective and/or delayed wound healing has been implicated in the pathogenesis of several chronic inflammatory disorders, including inflammatory bowel disease (IBD). The resolution of inflammation is particularly important in mucosal organs, such as the gut, where restoration of epithelial barrier function is critical to reestablish homeostasis with the interfacing microenvironment. Although IL-33 and its receptor ST2/ILRL1 are known to be increased and associated with IBD, studies using animal models of colitis to address the mechanism have yielded ambiguous results, suggesting both pathogenic and protective functions. Unlike those previously published studies, we focused on the functional role of IL-33/ST2 during an extended (2-wk) recovery period after initial challenge in dextran sodium sulfate (DSS)-induced colitic mice. Our results show that during acute, resolving colitis the normal function of endogenous IL-33 is protection, and the lack of either IL-33 or ST2 impedes the overall recovery process, while exogenous IL-33 administration during recovery dramatically accelerates epithelial restitution and repair, with concomitant improvement of colonic inflammation. Mechanistically, we show that IL-33 stimulates the expression of a network of microRNAs (miRs) in the Caco2 colonic intestinal epithelial cell (IEC) line, especially miR-320, which is increased by >16-fold in IECs isolated from IL-33–treated vs. vehicle-treated DSS colitic mice. Finally, IL-33–dependent in vitro proliferation and wound closure of Caco-2 IECs is significantly abrogated after specific inhibition of miR-320A. Together, our data indicate that during acute, resolving colitis, IL-33/ST2 plays a crucial role in gut mucosal healing by inducing epithelial-derived miR-320 that promotes epithelial repair/restitution and the resolution of inflammation.